Quo vadis, internal auditing? A vision for internal auditing in 2030 - Jokipii, Annukka; Rautiainen, Antti (John Wiley & Sons, 2023)
We aim to respond to calls in internal auditing (IA) literature and to the current changes in the IA field by describing the driving forces and vision of the future for IA in the year 2030. [Correction added on 24 August 2023, after first online publication: The definition of IA in the preceding sentence has been corrected in this version.] The goal was to prompt in-depth discussion informed by the divergent views of experts. As a contribution, we identify three key driving forces: prolific data and its application, globalization and new value chains between organizations. Further, the study reports a vision for the future of IA. By surveying a wide range of stakeholders, including the board, management, internal auditors, teachers and a legislator, we expand on the views in earlier literature regarding IA, IA developments and the application of Delphi argument analysis in voluntary IA context. The findings are of value in researching, planning, educating and developing IA activities to understand where IA is going and where divergences among stakeholders arise.
Keywords: change; corporate governance; Delphi; driving forces; education; future; stakeholders; internal auditing; internal control; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|